The Effect of Financial Performance and Capital Structure on the Company Value in Food and Beverage Companies Listed On The Indonesia Stock Exchange - Maria Afriani Manul; Muhamad Rifa'i; Moch. Nurhidayat (IRDH International Journal of Social Sciences & Humanities, 2025)
This study examines the relationship between capital structure, financial performance, and firm value using secondary data from 15 food and beverage companies listed on the Indonesia Stock Exchange (2021–2023). Data analysis includes multiple linear regression and assumption testing..  The findings indicate that a company's value is significantly increased by its financial performance, suggesting that more profitability increases its value.  Similar to how capital structure significantly affects firm value, a favourable debt-to-equity ratio also positively impacts a company's market perception. Moreover, capital structure and financial performance work together to influence corporate value. The findings above underscore the significance of investors considering a firm's profitability and capital structure when making investment choices to optimise returns. This report offers insights for research and investment plans by presenting data from Indonesia's food and beverage industry.